Analisis Implementasi Character Building di Sekolah Dasar Islam Terpadu Cut Nyak Dien Nagan Raya - Sitompul, Siti Jahria; Kesha, Cut Nabilla; Rizki, Julia; Ismar, Randila Tiayu; Srianturi, Yanuari (Lembaga Bale Literasi, 2026)
This study aims to analyze the implementation of character building at Cut Nyak Dien Integrated Islamic Elementary School in Nagan Raya. This includes an overview of the character education program implementation, an analysis of the program's evaluation system, identification of the program's impact on students and the institution, and the school's challenges and opportunities in implementing the program. This study employed a descriptive qualitative approach through three methods: in-depth interviews, observation, and documentation. The principal of Nagan Raya Integrated Islamic Elementary School was used for informant analysis. Data analysis used the interactive model of Miles, Huberman, and Saldana (2014). The findings of this study indicate that character building is implemented in four ways: the integration of all subjects (as per the Ministry of Primary and Secondary Education) with religion through the Quran and Hadith; the implementation of Islamic Personal Development (Bina Pribadi Islami, BPI) outside of school hours by teachers; monitoring student activity and reminding students if they do not demonstrate positive character traits as previously taught; and finally, the use of zero hour at school to strengthen character education. This program is evaluated daily by homeroom teachers and parents through a communication book. This character building program has a positive impact in forming positive characters in students inside and outside of school.